Echocardiographic diagnosis of atrial flutter in a neonate. Issue 9 (6th August 2018) - Low, Samantha; Kiper, Carmen; Armstrong, Aimee; Cua, Clifford L.
Abstract : A pregnant female presented at 37 weeks of gestation in labor. The fetus was noted to be tachycardic on fetal monitor. Postnatally, the male neonate was still noted to be tachycardic with heart rates in the low 200 bpm range. EKG was consistent with tachycardia, but rhythm diagnosis was not definitively made. Echocardiogram with M‐mode analysis clearly demonstrated 2:1 atrial to ventricular contraction pattern consistent with atrial flutter. The neonate was subsequently transferred to a tertiary pediatric hospital where the diagnosis of atrial flutter was confirmed.